2020
DOI: 10.1039/c9ra10232a
|View full text |Cite|
|
Sign up to set email alerts
|

Efficient broadband light absorption in thin-film a-Si solar cell based on double sided hybrid bi-metallic nanogratings

Abstract: Thin film solar cells (TFSCs) suffer from poor light absorption due to their small thickness, which limits most of their practical applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Among all experimented shape, we observed that sphere shape is the most optimized size of nanoparticle as shown in the figure. Beside the impact on absorption of light, sphere nanoparticles are capable of producing high, surface plasmons, polaritron, strong near field enhancement and larger scattering angle [8,9]. These are the most important parameters for enhanced current density.…”
Section: Impact Of Size Of Nanoparticle On Absorptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among all experimented shape, we observed that sphere shape is the most optimized size of nanoparticle as shown in the figure. Beside the impact on absorption of light, sphere nanoparticles are capable of producing high, surface plasmons, polaritron, strong near field enhancement and larger scattering angle [8,9]. These are the most important parameters for enhanced current density.…”
Section: Impact Of Size Of Nanoparticle On Absorptionmentioning
confidence: 99%
“…On the basis of advancement in technology solar cells can be divided into three generations namely first generation, second generation and third generation. First generation solar cells are known for their high-cost and high efficiency [8]. But production of first generation solar cells is a laboured task which is one of the major factor that are responsible for its high cost.…”
Section: Introductionmentioning
confidence: 99%
“…Recently light-trapping structures have been utilized in different ways to increase the absorption of plasmonic solar cells. Several structures including surface texturing [4][5][6], anti-reflection coatings [7,8], photonic crystals [9], nanogratings [10,11], and metallic nanoparticles [12][13] have been presented to enhance the absorption of plasmonic solar cells. Solar cells are generally classified into four generations [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…They have reported the highest absorption rate of >70% with corresponding current density of 22.30 mA/cm 2 . 15 In this work, we focused on enhanced solar cell performance with reduced optical losses by using natural abundant materials. The proposed design individually optimized thin-film layer thickness of ARC, top-SiO 2 and bottom-Ag diffraction nanogratings height, and a-Si region using RCWA method.…”
Section: Introductionmentioning
confidence: 99%